2021
DOI: 10.1002/gps.5607
|View full text |Cite
|
Sign up to set email alerts
|

How does carer management style influence the performance of activities of daily living in people with dementia?

Abstract: Introduction People with Dementia (PwD)'s performance of activities of daily living (ADLs) has been associated with apathy, cognitive deficits, carers' depression and burden. However, it is not known if the carers' management style affects ADL performance, particularly alongside PwD's cognitive deficits and apathy. Thus, the aim of this study was to explore the contribution of intrinsic (cognition, apathy) and extrinsic (carer management styles) dementia factors to ADL performance. Methods PwD (n = 143) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 28 publications
0
16
1
Order By: Relevance
“…This was a surprising finding given that the use of criticism style was found to negatively affect PwD's performance of daily tasks [14]. One way to explain this finding may be that criticism strategies are based on communication-related interactions, rather than providing actual support, and therefore its use had no effect on the comparative ADL score.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…This was a surprising finding given that the use of criticism style was found to negatively affect PwD's performance of daily tasks [14]. One way to explain this finding may be that criticism strategies are based on communication-related interactions, rather than providing actual support, and therefore its use had no effect on the comparative ADL score.…”
Section: Discussionmentioning
confidence: 91%
“…Caregivers' level of depression and anxiety had no effect on the comparative ADL score either. This can be attributed to the nature of the PwD's performance of daily tasks which is based on how their skills are affected by intrinsic dementia factors [14] and extrinsic factors such as the environment [31], rather than on the way the caregivers feel. Other studies have published contradictory results on the way depression affected caregivers' reports of ADL performance [6,7,11] and, to date, none of those studies measured the effect of caregiver level of anxiety on the discrepancy between informant and performance-based measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could comprise qualitative interviews at regular intervals and a brief objective measure of iADL with corresponding appraisal ratings; this would allow for a deeper understanding of how caregivers and people with dementia perceive iADL difficulties as well as help understand changes in caregiver adjustment, coping strategies, and stress/burden. This is especially salient as coping strategies, adjustment, and burden influence how informants rate iADL difficulties, 10,40,[45][46][47] and higher perceived stress is often associated with more perceived iADL difficulties. 3,10,15,17,19 How ratings accord with actual abilities is unknown, though a previous study found that people with mild-to-moderate dementia were able to rate performance on iADL tasks more accurately than corresponding ratings by their caregivers, particularly with tasks that do not largely rely on intact memory ability; for example, telling the time, or identifying medication.…”
Section: Discussionmentioning
confidence: 99%
“…This could comprise qualitative interviews at regular intervals and a brief objective measure of iADL with corresponding appraisal ratings; this would allow for a deeper understanding of how caregivers and people with dementia perceive iADL difficulties as well as help understand changes in caregiver adjustment, coping strategies, and stress/burden. This is especially salient as coping strategies, adjustment, and burden influence how informants rate iADL difficulties, 10 , 40 , 45 , 46 , 47 and higher perceived stress is often associated with more perceived iADL difficulties. 3 , 10 , 15 , 17 , 19 …”
Section: Discussionmentioning
confidence: 99%